Le Corporatisme de l’État Nouveau Portugais. Un débat sur l’institutionnalisation économique de la Nation - Álvaro Garrido (Storicamente, 2015)
This article aims to discuss the nature of the Portuguese corporatist experience built under the so called «New State» (1933-1974). Using some primary sources and theoretical bibliography on the Portuguese corporatist system, the article examines how the corporatist ideology was expressed in the building process for a «national corporatist economy». Above this question, facing the common propaganda used by the dictatorship regimes on their economic nationalism, we debate the political links between the Portuguese dictatorship institutions and the economic “corporatist organization”.